First record of Eunotosaurus (Amniota: Parareptilia) from the Eastern Cape. - Gow, Chris E.; de Klerk, Billy (Bernard Price Institute for Palaeontological Research, 1997)
Eunotosaurus is a rare tetrapod fossil until recently known only from the Tapinocephaluszone of the main Karoo basin of Cape Province. A single specimen has recently been collected in the Free State (Weiman, pers. com.). This paper describes a new find from the Eastern Cape, where outcrops of Karoo rocks are scarce. The new specimen adds previously unknown morphological detail, particularly about the limbs. Phylogenetic affinities are clearly with the Parareptilia. particularly about the limbs. Phy logene tic affinities are clearly with the Parareptilia.
Main article
Keywords: Eunostosaurus, parareptiles